The impact of external financial liberalization on financial inclusion in Egypt over the period: 2004-2021 by using access indicators - Benkari, Samir; Djerbi, Abdelhakim; Yassine, Mostefai; Moustefa, Boudrama (The International tax journal, 2025)
This study aims to know the impact of external financial liberalization on financial inclusion in the Arab Republic of Egypt. In order to know this relationship, we relied upon three indicators that reflect external financial liberalization, which were built on the basis of foreign direct investment, investment in the financial portfolio and exchange rates, while the financial inclusion index was adopted as a composite index using the basic components analysis method. Using the least squares method, we reached the conclusion that there is a statistically significant negative relationship between investment in the financial portfolio and the financial inclusion index on the one hand, and the same thing applies to unemployment, while the financial inclusion index was not affected by the rest of the external financial liberalization indicators.